2014
DOI: 10.1038/tpj.2014.57
|View full text |Cite
|
Sign up to set email alerts
|

The first steps towards the era of personalised vaccinology: predicting adverse reactions

Abstract: Until now, the occurrence of adverse reactions among individuals inoculated with identical vaccines has been ascribed to unpredictable stochastic processes. Recent advances in pharmacogenomics indicate that some features of host response to immunisation are influenced by genetic traits, henceforth predictable. The ability to predict the adverse reaction to vaccination would represent an important step towards the development of personalised vaccinology and could enhance public confidence in the safety of vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…The role of genetic predisposition in the risk of occurrence of vaccine-related adverse reactions has been discussed largely in recent years [21,50,77,78], with special emphasis on the ''ASIA-Autoimmune/inflammatory Syndrome Induced by Adjuvants'' [79]. The term ''ASIASyndrome'' was coined in 2011 to describe the spectrum of immune-mediated diseases triggered by an adjuvant stimulus [79][80][81][82][83][84][85][86].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of genetic predisposition in the risk of occurrence of vaccine-related adverse reactions has been discussed largely in recent years [21,50,77,78], with special emphasis on the ''ASIA-Autoimmune/inflammatory Syndrome Induced by Adjuvants'' [79]. The term ''ASIASyndrome'' was coined in 2011 to describe the spectrum of immune-mediated diseases triggered by an adjuvant stimulus [79][80][81][82][83][84][85][86].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have been reported on this topic, including significant evidence about the role of several SNPs in cytokines production following vaccinations [44][45][46][47][48][49][50].…”
Section: The Molecular Mechanismmentioning
confidence: 98%
See 1 more Smart Citation
“…A growing body of literature points to influence of human genetic variability on efficacy as well as tolerability/ adverse effects of a number of vaccines (reviewed in ref. (59,63,71,72)). Specifically, associations of variations in human genes for HLA, cytokines, or cytokine receptors, molecules associated with mounting immune response, have been implicated in determining response to hepatitis B vaccine (73)(74)(75)(76), hepatitis C vaccine (77)(78)(79) as well as a number of childhood vaccines including rubella (80), mumps (81,82), and measles (81)(82)(83), as well as malaria (84).…”
Section: Discussionmentioning
confidence: 99%
“…However, these drugs represent a small fraction of the current and growing list of BTs on the market (10-12). Several technical, logistic, and regulatory factors have been cited as possible barriers (56)(57)(58)(59)(60)(61)(62)(63). Some of these challenges appear to be common both small and large molecule drugs.…”
Section: From Pgx Of Small Molecule Therapeutics To Pgx Of Btsmentioning
confidence: 99%